Indigenous Knowledge, Gender and Agriculture: A Scoping Review of Gendered Roles for Food Sustainability in Tonga, Samoa, Solomon Islands and Fiji - Jasmina Thomas; Nidhi Wali; Nichole Georgeou; Seeseei Molimau-Samasoni (Land, 2025)
This scoping review examines the state of academic knowledge around gender and its role in Indigenous/traditional knowledge for food sustainability in Tonga, Samoa, Solomon Islands and Fiji. The different roles played by all genders—men, women and non-binary—in the Pacific Islands can contribute to climate adaptation and knowledge preservation for sustainable food production. The gender lens is especially relevant given the fact that women’s knowledge has, in recent years, been disregarded and marginalised as a consequence of colonial influences and increasing reliance on imported foods. We analysed 14 studies published in English between 2015 and 2024—six from refereed journal articles and eight from grey literature. Three themes emerged linking agriculture, gender and traditional knowledge, as follows: (1) there is a gendered division of labour and culturally defined roles between women and men, although the roles played by non-binary groups remain unclear; (2) intergenerational traditional knowledge transmission has declined; (3) climate change adaptation could be reinforced through passing on traditional knowledge. The findings demonstrate that gendered knowledge is distinct and complementary, and this knowledge should be integrated into Pacific agricultural production to achieve resilient and sustainable farming in the face of climate change.